Perovskite Manganit Analysis Based on La0.7Ca0.3Mn1-xTixO3 (x=0, 0.1, 0.2, and 0.3) as Potential Microwave Absorber Material with Sol-Gel Method - Fira Rizky; Sitti Ahmiatri Saptari; Arif Tjahjono; Deni Shidqi Khaerudini (Universitas Sebelas Maret, 2022)
Electromagnetic wave is an energy flow in the form of electric and magnetic field as the technology development causes electromagnetic wave exposure level changes significantly and resulting an electromagnetic wave radiation that leads bad impacts on human health. In this case, manganite perovskite became an interesting topic of study that aims to produce material engineering to obtain a material with the best property as absorber. This study is based on lanthanum manganite La0.7Ca0.3Mn1-xTixO3 ( and ) using sol-gel method with the with a heating temperature in the oven of 200oC for 2 hours, calcination temperature of 600oC for 6 hours, and sintering temperature of 1000oC for 12 hours. The sample is characterized using X-Ray Diffraction (XRD) that shows the sample had succeeded to form single phase and had crystal cubic structure with space group p m -3 m, the substitution of Ti3+ions did not cause the structural changes, but it was marked with the changes of lattice parameter, unit cell volume and average crystallite size. Meanwhile Vector Network Analyzer (VNA) on the frequency range 8-12 GHz shows that the sample has ability to absorb microwave until 90.16% on 10.4 GHz frequency. Therefore, the material based on lanthanum manganite La0.7Ca0.3Mn1-xTixO3has the potential as the microwave absorber material.